The Water Conserving Practices of Households in Katchi Abadis of Lahore: A Gender-Based Analysis - Asma Seemi Malik; Shehla A Yasin; Samina Riaz; Amjad Mahmood (ASIAN Journal of International Peace & Security (AJIPS), 2021)
Water is a basic human need but the world is increasingly confronted with the greatest water crisis. The behavior of individuals is the true face of this crisis. The focal point of this cross-sectional quantitative study was to contemplate the attitude and habits of people in slum households in a gender-based context on how to conserve water in Lahore. Specifically, the study looked at two primary objectives. Firstly, to explain gender dissimilarity in attitude to conserve water and, secondly, to investigate gender differences in residential water conservation habits. Two slums were selected for comparison. Structured questionnaires containing close statements were used. A total sample of 200 respondents both male (100) and female (100), 50 each male and female within the age bracket of 18-65 years from a permanent household with 3-8 family members in both localities were selected. In current work, Dolnicar et al.’s (2012) attitudes and patterns scales and Past Habit scale by Sathaporyajana (2008) was employed. The findings showed that even though the mainstream of the family unit settled on the fact that water saving is necessary to sustain water resources, but a difference was seen in the responsibilities of both males and females.